Clinical Characteristics and Prognostic Factors of Cranial Gunshot Injuries during July Uprising in Bangladesh: A Retrospective Study from Dhaka Medical College Hospital (Bangladesh Critical Care Journal, 2025)
Background: Cranial gunshot injuries are a leading cause of severe morbidity and mortality, particularly in regions marred by political unrest and violence. During the July Revolution 2024 in Bangladesh, a mass uprising against governmental repression, thousands of innocent civilians were targeted in brutal crackdowns, resulting in widespread gunshot injuries, many of which involving head. Dhaka Medical College Hospital became a frontline facility for managing these critical injuries. This study aims to evaluate the clinical characteristics and prognostic indicators of cranial gunshot injury patients admitted during July Uprising in Bangladesh. Methodology: This retrospective study analyzed ICU registry data from Dhaka Medical College Hospital between July 18 and August 8, 2024, focusing on cranial gunshot injury patients with confirmed CT scans. Key variables such as demographics, GCS scores, clinical parameters, and radiological findings were assessed. Multiple logistic regression identified predictors of GOS scores, and a risk model was developed and validated using the Hosmer-Lemeshow test with data analysis conducted in SPSS 26. Results: The study aimed to identify factors predicting favourable outcomes in patients with cranial gunshot injuries. The patients had a mean age of 26.5 ± 11.83 years, with a predominant male population (97.9%). Initial GCS was 8±2, and 85.4% required mechanical ventilation. Baseline vital parameters included a mean MAP of 61 ± 20 mmHg, SpO2 of 82 ± 12%, and blood sugar of 6.6 ± 2.8 mmol/L. Logistic regression revealed that initial Glasgow Coma Scale (GCS) (p = 0.003) and SpO2 (p = 0.015) were significant predictors of favourable outcomes. A 1-point increase in GCS increased the odds of a favourable outcome by 65%, and each 1% increase in SpO2 improved outcomes by 3%. Age, sex, mechanical ventilation, MAP, and blood sugar were not significant predictors (p > 0.05). Model adequacy was confirmed by a Nagelkerke’s R² of 0.48, indicating that 48% of the variance in outcomes was explained by the predictors, and Hosmer-Lemeshow test (p = 0.71) indicated a good fit. CT scan findings showed that subarachnoid haemorrhage, spinal cord injury, and acute subdural hematoma were significant predictors of unfavourable outcomes. Specifically, subarachnoid haemorrhage had the strongest negative association (OR = 0.11, p = 0.010), followed by acute subdural hematoma (OR = 0.14, p = 0.025). Overall, GCS and SpO2 were key factors in predicting outcomes, while CT findings revealed critical structural injuries as strong predictors of poor prognosis. Conclusion: This study highlights the critical role of initial GCS scores and SpO2 levels as significant predictors of favourable outcomes in patients with cranial gunshot injuries. Radiological findings such as subarachnoid haemorrhage, spinal cord injury, and acute subdural hematoma were associated with unfavourable outcomes, emphasizing the importance of early and precise imaging. The findings underline the need for targeted interventions and resource allocation in conflict zones to optimize trauma care and improve survival rates.Bangladesh Crit Care J March 2025; 13 (1): 4-10